Wages in the East German transition process: facts and explanations - Wolfgang Franz; Viktor Steiner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
We analyze wage developments in the East German transition process both at the macro and at the microeconomic level. At the macroeconomic level, we draw special attention to the important distinction between product and consumption wages, describe the development of various wage measures, labor productivity and unit labor costs in East Germany in relation to West Germany, and relate these developments to the system of collective wage bargaining. At the microeconomic level, we describe changes in the distribution of hourly wages between 1990 and 1997 and analyze the economic factors determining these changes by way of empirical wage functions estimated on the basis of the Socio? Economic Panel for East Germany. The paper also draws some conclusions on the likely future course of the East-West German wage convergence process.
Keywords: P51; J24; J31; 330; Lohn; Lohnstruktur; Arbeitsproduktivität; Arbeitskosten; Wirtschaftliche Anpassung; Neue Bundesländer